Die plek, taak en terrein van die mediakundige in universiteitsonderwys - Oosthuizen, S. J. P.(Stephanus Johannes Paulus) (Stellenbosch : Stellenbosch University, 2012)
Proefskrif (M. Ed.) -- Universiteit van Stellenbosch, 1984.